Facile and scalable synthesis of Ti₅Si₃ nanoparticles via solid-state route in an autoclave - Mao, W.; Bao, K.; Cao, F.; Ye, L.; Xie, H.; Li, B.; Wang, W. (Сверхтвердые материалы, 2017)
A novel method of the synthesis of titanium silicide nanoparticles via solid-state route in an autoclave at 700 °C is reported. The reaction of titanium silicide could be described briefly as: 5TiO₂ + 3Si + 20Li = Ti₅Si₃ + 10Li₂O. XRD pattern indicated that the product was hexagonal Ti₅Si₃. The Ti₅Si₃ particle size (about 20–40 nm) is confirmed by the TEM images. Furthermore, the thermal stability and oxidation resistance of the titanium silicide nanoparticles were also investigated.